Immune defects in patients with pulmonary Mycobacterium abscessus disease without cystic fibrosis. Issue 4 (10th November 2020) - Schuurbiers, Milou M.F.; Bruno, Mariolina; Zweijpfenning, Sanne M.H.; Magis-Escurra, Cecile; Boeree, Martin; Netea, Mihai G.; van Ingen, Jakko; van de Veerdonk, Frank; Hoefsloot, Wouter
The prevalence of Mycobacterium abscessus infections in non-cystic fibrosis (CF) patients has increased in recent years. In this study, we investigate whether immune defects explain the apparent susceptibility to this opportunistic infection in non-CF patients. We performed stimulations of peripheral blood mononuclear cells and whole blood from 13 patients with M. abscessus pulmonary disease and 13 healthy controls to investigate their cytokine production after 24 h and 7 days. Patients were predominantly women (54%) with a mean age of 59 years; 62% had nodular bronchiectatic disease. Many patients had predisposing pulmonary diseases, such as COPD (46%), and asthma (23%). Patients with COPD showed an impaired interleukin (IL)-6 response to M. abscessus and a reduced IL-17 response to Candida, together with a M. abscessus -specific enhanced IL-22 production. Patients without COPD showed higher levels of interleukin-1 receptor antagonist (IL-1Ra), an anti-inflammatory molecule. Within the non-COPD patients, those with bronchiectasis showed defective interferon (IFN)-γ production in response to Candida albicans . In conclusion, susceptibility to M. abscessus is likely determined by a combination of immunological defects and predisposing pulmonary disease. The main defect in the innate immune response was a shift of the ratio of IL-1β to IL-1Ra, which decreased the bioactivity of this pathway in the adaptive immune response. In the adaptive immune response there was defective IL-17 and IFN-γ production. Patients with COPD and bronchiectasis showed different cytokine defects. It is therefore crucial to interpret the immunological results within the clinical background of the patients tested. Measurement of defects in both the innate and adaptive immune responses in patients with M. abscessus pulmonary disease show that susceptibility to M. abscessus is determined by a combination of immunological defects and predisposing pulmonary disease https://bit.ly/2DtbycY